Next generation multi-screen interactive technology system of smart home based on TV screen - Weijia SHI; Zheng WEI; Guqiao ZHU (Dianxin kexue)
With the full popularity of internet technology and the rapid development of video services,video content has become the current home entertainment protagonist.With the diversity of terminals and the improvement of display technology,the carrier of video services is no longer a single television.Based on the operator’s IPTV service,combined with the development trend of smart home business,the core elements of the multi-screen interactive technology architecture of the next-generation video service were described in detail,the next-generation multi-screen interactive service with the core of TV screen was introduced,and the combination of future video multi-screen business and other emerging technologies was look forward.